Comparison of skeletal changes related to patients with chronic kidney disease and healthy individuals in digital panoramic radiography - Mehrdad Abdinian; Mojgan Mortazavi; Zahra Jandaghian (Wolters Kluwer Medknow Publications, 2019)
Background: Chronic kidney disease (CKD) is a prevalent condition affecting bone metabolism. Bone changes in CKD patients also known as renal osteodystrophy happen due to disorders in the regulation of water and electrolytes caused by the disease. The aim of this study is to investigate the bone changes of CKD stages 3-5 patients without dialysis using digital panoramic radiography. Materials and Methods: In this cross-sectional study, panoramic radiographs were obtained from 30 patients with CKD stages 3-5 and 30 age and gender matched healthy individuals. The mean values of quantitative parameters such as mental index (MI), panoramic mandibular index (PMI), and antegonial index (AI) were measured and qualitative parameters such as mandibular cortical index (MCI) and trabecular bone pattern (TP) were recorded based on Kelemetti and Lindh calcifications, respectively. Statistical analysis was performed using t-test, Chi-square, and Mann-Whitney test (α = 0.05). Results: The mean values of MI, PMI, and AI in the two groups were not statistically significant (P > 0.05). MCI and TP were significantly different between the two groups. MCI showed more defects in mandibular cortex of CKD patients (6.7% of patients vs. 0% of control group were C3, P = 0.038), and TP showed more porosity in mandibular bone of CKD patients (10% of patients vs. 0% of control group were sparse, P = 0.001). Conclusion: The amount of MI, PMI, and AI were not related to CKD. While MCI and TP were significant parameters that showed mandibular cortical situation and trabecular bone pattern, they assess osteoporosis level in a more reliable manner in CKD stages 3-5 patients without dialysis.